Social Interaction Between Malay and Buton Ethnic in Tanjung Gunung Village, Bangka Tengah Regency - Helen Anjelina (Green Publisher Indonesia, 2021)
The pattern of displacement carried out by the community triggers the increasing diversity in Indonesia. Be it in terms of culture, religion, ethnicity, and so on. Just like what happened in Tanjung Gunung Village where there are Malay and Buton ethnicities. The research aims to find out the social interaction between Malay and Buton ethnic groups in Tanjung Gunung Village, Bangka Tengah Regency. The method used in this research is by qualitative approach with descriptive method. Data collection techniques used are observation techniques, interviews, and documentation studies. While data collection tools are observation guides, interview guides, and documentation. The results showed that social interactions that occurred between Malay and Buton ethnicity led to dissociative social processes. This is demonstrated by the pattern of interaction in the form of competition and conflict between the two ethnicities